2023
DOI: 10.21608/jocc.2023.307055
|View full text |Cite
|
Sign up to set email alerts
|

Fit Moi: Online Virtual Fitting Room With Texture Identification And Recommendation System

Diaa AbdElminaam,
yasmin mohamed,
salma osama
et al.

Abstract: Virtual fitting rooms have attracted the sights of the market need in the past two years; The world faced a colossal pandemic that led everything to be online. This proposed framework aims to solve the online shopping problem using deep learning algorithms and techniques. Users face significant issues, whether finding the perfect fit, recognizing the fabric, or styling their outfits. As a result, merchants' profit is impacted, resulting in a high percentage of returns. This proposed model aims to generate a 3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Omkar et al [29] in 2023 have combined AR with DL to build a VFR. The authors confirmed that their approach that renders the image cloth on the customer's image improved the customer's experience, but they also mentioned nothing factual about their results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Omkar et al [29] in 2023 have combined AR with DL to build a VFR. The authors confirmed that their approach that renders the image cloth on the customer's image improved the customer's experience, but they also mentioned nothing factual about their results.…”
Section: Literature Reviewmentioning
confidence: 99%